Integration of an energy storage system in a wind farm, case study - Araya Rodríguez, Jorge David (2022)
Wind energy must be transformed instantaneously; it does not allow direct storage like hydroelectric energy. In a wind farm, it is possible to take advantage of the surplus energy generated during the night, when there is less demand, through an energy storage system with batteries. This work establishes the type of technology that meets the ideal characteristics, the power and energy dimensioning, as well as the financial viability of installing a battery bank in a wind farm, considering the maximum curve of the distribution network and the discharge time. It is found that a system of 2.5 MW of nominal power is required, which operates for 2.5 hours, which represents a total energy of 6.25 MWh. Lithium-Ion and Vanadium Redox Flux technologies are selected as the technologies that present the best results for this system. This selection was made considering the history of the electrical distribution system, discharge depth, annual degradation, installation configuration and energy density. Two types of installation are proposed: complete and postponed. The second allows to adapt each system according to the network and the degradation of the battery bank. It is found that the investment is around $ 8 million and it is concluded that despite being a feasible solution to the use of surpluses, under the conditions analyzed the investment is not justifiable. It is recommended to assess the investment in the future when the costs of storage technologies decrease.